2006
DOI: 10.1017/s0033291706009019
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood factors associated with the development of post-traumatic stress disorder: results from a longitudinal birth cohort

Abstract: Background-Childhood factors have been associated with increased risk of developing posttraumatic stress disorder (PTSD). Previous studies assessed only a limited number of childhood factors retrospectively. We examined the association between childhood neurodevelopmental, temperamental, behavioral and family environmental characteristics assessed before age 11 years and the development of PTSD up to age 32 years in a birth cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
226
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(243 citation statements)
references
References 37 publications
13
226
1
3
Order By: Relevance
“…In a parallel fashion, longitudinal studies that document the long-term consequences of childhood adversity indicate that alterations in a child' s ecology can have measurable effects on his or her developmental trajectory, with lifelong consequences for educational achievement, economic productivity, health status, and longevity. [23][24][25][26][27] The EBD framework described in this article presents a new way to think about the underlying biological mechanisms that explain this robust link between early life adversities (ie, the…”
Section: A New Framework For Promoting Healthy Developmentmentioning
confidence: 99%
“…In a parallel fashion, longitudinal studies that document the long-term consequences of childhood adversity indicate that alterations in a child' s ecology can have measurable effects on his or her developmental trajectory, with lifelong consequences for educational achievement, economic productivity, health status, and longevity. [23][24][25][26][27] The EBD framework described in this article presents a new way to think about the underlying biological mechanisms that explain this robust link between early life adversities (ie, the…”
Section: A New Framework For Promoting Healthy Developmentmentioning
confidence: 99%
“…No data Post-traumatic stress Koenen et al (2007) Age o5 years childhood risks : 50 % develop PTSD after trauma ; 8 % after only 1 year Koenen et al (2003) Neglect, sexual and physical abuse are at increased risk for developing PTSD Widom (1999) Family, individual and lifestyle variables also place individuals at risk Breslau (2002) Traumas sufficient to cause PTSD very common, those who do not develop PTSD after trauma are not at increased risk of MDD Craig et al (2004) Mothers reported frequent headaches and stomachache in childhood ; were emotionally flatter Egle & Nickel (1998) Parents more frequently chronically ill or disabled, more sexual and physical abuse and family disharmony GAD, Generalized anxiety disorder ; MDD, major depressive disorder ; OCD, obsessive-compulsive disorder ; PTSD, post-traumatic stress disorder ; OR, odds ratio. have reported multivariate analyses of self-report instruments of these disorders find a large general distress factor running across items, and this has been variously named ' neuroticism ' (Eysenck, 1964 ; and many other authors), ' negative emotionality ' (Harkness et al 1995) and ' negative affectivity ' (Watson et al 1984).…”
Section: Dysthmic Disorder No Data Neurasthaeniamentioning
confidence: 99%
“…Our study had a number of strengths, the most notable of which was an increased capacity to perform tests of gender interaction. We were also able to account for trauma type with increased specificity compared with previous studies (Breslau, et al, 2006;Koenen, et al, 2007;Storr, et al, 2007) by controlling for multiple trauma exposure, which has been shown to increase the risk of PTSD (Copeland, Keeler, Angold, & Costello, 2007). Another important strength was the age at which we attained measures.…”
Section: Discussionmentioning
confidence: 98%
“…One study from Storr and colleagues has found no association between early scholastic ability and PTSD (Storr, Ialongo, Anthony, & Breslau, 2007). The other two studies have found inverse associations between cognitive ability with PTSD risk in late adolescence (Breslau, Lucia, & Alvarado, 2006) and early adulthood (Koenen, Moffitt, Poulton, Martin, & Caspi, 2007). There were some methodological 6 This is a post-print version of the following article: Betts, Kim Steven, Williams, Gail M., Najman, Jacob M., Bor, William and Alati, Rosa (2012) Pre-trauma verbal ability at five years of age and the risk of post-traumatic stress disorder in adult males and females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation